Effects of Steaming on the Functional Properties and Mineral Content of Lumi-Lumi Fish (Harpodon Nehereus) Meal - Safrida, Safrida; Rahma, Cukri; Putra, Onetusfifsi; Rinawati, Rinawati; Nurtiana, Winda; Kurniati, Yeni (Universitas Teuku Umar, 2023)
The purpose of this study is to evaluate the mineral content, phenolic content, antioxidant activity, and soluble protein of Lumi-lumi fish meal (Harpodon nehereus) treated with and non-steamed for 30 min. The results revealed that iron (Fe) mineral content was significantly higher in the steamed than non-steamed treatment but not in calcium (Ca). However, there was a decrease in the minerals magnesium (Mg), phosphorus (P), and zinc (Zn) during the steamed process, which was not significant. Then, during steamed, there was a significant decrease in antioxidant activity but not in total soluble protein, whereas phenolic content increased. Based on the findings of this study, Lumi-lumi fish (Harpodon nehereus) meal steamed treatment could be the best treatment because it contained the best phenolic and Fe and Ca minerals.